Anti-Hoax Election Prebunking Training and Campaign for Novice Voters - Ellisa Vikalista; Sri Astuty; Nur Tazkia Amalia Hamdie; Gusti Amalia Primadina; Sarwani Sarwani (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The 2024 general elections in Indonesia encounter the issue of a significant number of novice voters as the main consumers of social media, making them susceptible to hoaxes. On that basis, approaches are needed to reduce the possibility of exposure to hoaxes through prebunking. Training in Prebunking Classes and Prebunking Campaigns was held to form antibodies among novice voters to increase resistance to exposure to misinformation, disinformation, and misinformation circulating ahead of the 2024 Election. This training, in collaboration with the anti-hoax organization Mafindo Banjarmasin, took place concurrently on Thursday, October 05, 2023, with 320 participants. The training sessions utilitized the PRA (Participatory Rural Appraisal) approach and were segmented into three stages, which were: (1) the initial stage involved coordinating activities between the campus and Mafindo Banjarmasin regarding the implementation of activities; (2) the implementation stage, Prebunking Class activities were divided into four sessions with topics such as mapping disinformation and misinformation narratives, analyzing the anatomy of information manipulation, pre bunking theory and strategies, and producing pre bunking content. Meanwhile, the Prebunking Campaign activities were carried out by playing the Ular Tangga boardgame, which contained quizzes and tips on anticipating hoaxes; and (3) the last stage evaluated the effectiveness of the training through pretest and post-test examinations, along with feedback from participants. The outcome of the activity involved increased empowerment among novice voters in recognizing different election hoaxes and acquiring a better understanding of manipulative information tactics. Armed with this knowledge, the training instils stronger resistance strategies against exposure to election hoaxes in novice voters.